Diaphragm Relaxing Incisions in Repair of Hiatal Defects—When to Relax and How to Achieve Closure. Issue 1 (March 2022) - Hodges, Maggie M.; DeSouza, Melissa M.; Reavis, Kevin M.; DeMeester, Steven R.; Dunst, Christy M.; Davila-Bradley, Daniel
The operative challenges presented by large hiatal defects require that surgeons have an expansive armamentarium of tools with which to approach the crural closure. When crural closure cannot be achieved primarily, our experience suggests that use of diaphragm relaxing incisions can facilitate primary crural closure, contributing to decreasing the risk of recurrence following hiatal or paraesophageal hernia repair. Here, we present our method for identifying patients who would benefit from a diaphragm relaxing incision, as well as the technique for performing both a right and left diaphragm relaxing incision.